2015
DOI: 10.1371/journal.pgen.1005534
|View full text |Cite
|
Sign up to set email alerts
|

Insect Resistance to Bacillus thuringiensis Toxin Cry2Ab Is Conferred by Mutations in an ABC Transporter Subfamily A Protein

Abstract: The use of conventional chemical insecticides and bacterial toxins to control lepidopteran pests of global agriculture has imposed significant selection pressure leading to the rapid evolution of insecticide resistance. Transgenic crops (e.g., cotton) expressing the Bt Cry toxins are now used world wide to control these pests, including the highly polyphagous and invasive cotton bollworm Helicoverpa armigera. Since 2004, the Cry2Ab toxin has become widely used for controlling H. armigera, often used in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 116 publications
2
127
1
2
Order By: Relevance
“…Expression of other Bt-toxin binding proteins such as aminopeptidase [47,48,49] or cadherin [18,19] has a much weaker effect. Recently, several mutations in ABCA2, a member of the A subfamily of ABC proteins, were found to confer high resistance against Cry2Ab1 in two Lepidoptera, Helicoverpa armigera and H. punctigera [13]. Our study adds a third subfamily of ABC proteins and a different toxin, active against Coleoptera but not Lepidoptera, to this interaction.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Expression of other Bt-toxin binding proteins such as aminopeptidase [47,48,49] or cadherin [18,19] has a much weaker effect. Recently, several mutations in ABCA2, a member of the A subfamily of ABC proteins, were found to confer high resistance against Cry2Ab1 in two Lepidoptera, Helicoverpa armigera and H. punctigera [13]. Our study adds a third subfamily of ABC proteins and a different toxin, active against Coleoptera but not Lepidoptera, to this interaction.…”
Section: Discussionmentioning
confidence: 68%
“…A previous report indicated that, in C. tremula , there was no difference in sequence and in expression of three APNs between insects of the susceptible and the resistant strains [10]. We turned to ABC proteins because of their association with resistance to Cry1A and Cry2A toxins in Lepidoptera [11,12,13,14]. We used a recent analysis of the tissue-specific expression of genes encoding ABC proteins in C. populi , a sister species of C. tremula , to identify ABC proteins expressed in the larval midgut.…”
Section: Resultsmentioning
confidence: 99%
“…There has been much interest recently in the interaction of Cry toxins with members of the ATP binding cassette (ABC) protein family, particularly subfamilies C2 and A. Alterations in these ABC proteins are linked with resistance against Cry1 toxins (Heckel, 2012;Park et al, 2014;Xiao et al, 2014) and Cry2Ab (Tay et al, 2015). Although the exact role of these proteins remains unclear it has been proposed that they may act as receptors but only when in a particular conformational state (Heckel, 2012) …”
Section: Specificity Level Vi: Binding To Receptorsmentioning
confidence: 99%
“…In lepidopteran insects, four major Cry1A toxin protein receptors have been identified – cadherins, ABCC transporters, aminopeptidases (APNs) and alkaline phosphatases (ALPs) (Atsumi et al 2012; Bravo et al 2011; Gahan et al 2010; Pardo-Lopez et al 2012; Pigott and Ellar 2007; Soberon et al 2009; Tay et al 2015). APN and ALP are thought to be receptors that facilitate localization of toxin monomers to midgut microvilli before toxin interaction with cadherin.…”
Section: Introductionmentioning
confidence: 99%